Factors and causes of the occurrence and development of accidents at oil products supply facilities - A. V. Zhuravlev; S. N. Kholodova; D. A. Rudikov (Безопасность техногенных и природных систем, 2019)
The article analyzes the factors and causes of the occurrence and development of accidents at oil products supply facilities. It is shown that the main causes and factors of accidents are the presence of large amounts of oil and oil products at the facility, which are explosive and flammable substances, transportation of oil products under high pressure, operation of equipment under pressure at high temperatures, the presence of periodic processes and transient conditions of equipment as well as the corrosive activity of oil and oil products (especially with sulfur compounds).